Opportunities and challenges harnessing antigen-specific CD4+ regulatory T cells in inflammatory bowel disease - Kümmel, Jessica; Schlegel, Nicolas; Wagner, Johanna C. (Frontiers in Immunology, 2025)
Inflammatory bowel diseases (IBD), including Crohn´s disease (CD) and ulcerative colitis (UC) remain highly prevalent and are associated with a reduced quality of life in affected patients. The pathophysiology of IBD is multifactorial since genetic predisposition, altered immune function, changes in intestinal microbiota, environmental factors, and loss of intestinal barrier function together induce disease manifestation. A critical key factor is the dysregulation of the immune system which explains that all medical therapeutic approaches target the immune response. However, the success of these therapies is limited and associated with severe side effects which demonstrates the need for novel therapeutic approaches. Previous research demonstrated that CD4+ regulatory T (Treg) cells are important regulators of intestinal homeostasis but are reduced in number and function relative to effector T cells in IBD. This led to the concept that genetically engineered, antigen-specific Tregs may represent a promising strategy to address immune dysregulation in IBD. Due to their antigen specificity, chimeric antigen receptors (CARs) enable additional target-dependent activation and migration of Tregs at disease sites. While CARs are increasingly established for the generation of antigen-specificity for T cell therapies in cancer, the implementation of CARs for IBD is in a preliminary state. Nonetheless, CAR constructs specific to circulating carcinoembryonic antigen (CEA), flagellin, or IL23R have been developed recently for potential application in IBD. Based on these novel developments, this review will discuss the role of Tregs in IBD disorders and present the current state of CAR Treg models.